Soya Milk Using for Herbivorous Fishes Larvae Raring - N.R. Toshova; O.T. Nosirov; B.G. Kamilov; M.A. Yuldashov (Zien Journals, 2022)
In ponds (3 ha) with brackish water, larvae of silver carp (Hypophthalmichthys molitrix) and bighead carp (H. nobilis) were grown in monoculture. There were stocked silver carp larvae - 2 million pieces, bighead carp - 0.5 million pieces. Soy milk was prepared daily (15 kg of beans/pond/day + 140 l of water in each pond) and applied to the pond for 30 days. The yield from the first pond was 900,000 fry of the silver carp with a total biomass of 4104 kg, from the second - 210,000 bighead carp with a total biomass of 1070 kg (yield 45% and 42%, respectively).
Keywords: aquaculture; silver carp; bighead carp; soybean milk